In vitro micropropagation and allelopathic effect of lantana (Lantana camara L.) - Veraplakorn, Varaporn (Agriculture and Natural Resources, 2017)
The invasive plant, lantana (Lantana camara L.), is well known as a traditional medicinal plant and it may become important in the development of modern drugs. Lantana has long been touted as containing potent allelochemicals and in vitro-produced tissues may be appropriate sources for the production and isolation of bioactive compounds. In this research, effective techniques for shoot multiplication and root and callus induction were developed and the allelopathic efficiency of in vitro leaf and callus was examined. The optimized medium for shoot multiplication was Murashige and Skoog (MS) medium supplemented with 12.0-20.0 µM thidiazuron. For rooting, high root numbers were obtained on MS medium containing 5.0 or 10.0 µM 1-naphthalene acetic acid (NAA). In addition, the highest relative growth rate of callus was achieved when lantana leaf was cultured on NB medium (MS medium with 21.5 µM NAA and 22.5 µM N6-benzyladenine). For allelopathic effects, the results suggested high potential activity of lantana leaf and callus that was able to variably inhibit the seed germination and seedling growth of all four test species. Leaf and callus extract had no significant effect on the germination of Brassica campestris var. chinensis. Callus extract showed superior ability to suppress germination for Ipomoea aquatica Forsk. and Zea mays L. but inferior inhibition ability for Sorghum bicolor L. These results suggested that the extract of lantana in vitro leaf and callus will be an interesting natural source for further study to develop natural herbicides.